Three suggestions on the definition of terms for the safety and reliability analysis of digital systems. (March 2015) - Kim, Man Cheol; Smidts, Carol S.
Abstract: As digital instrumentation and control systems are being progressively introduced into nuclear power plants, a growing number of related technical issues are coming to light needing to be resolved. As a result, an understanding of relevant terms and basic concepts becomes increasingly important. Under the framework of the OECD/NEA WGRISK DIGREL Task Group, the authors were involved in reviewing definitions of terms forming the supporting vocabulary for addressing issues related to the safety and reliability analysis of digital instrumentation and control (SRA of DI&C). These definitions were extracted from various standards regulating the disciplines that form the technical and scientific basis of SRA DI&C. The authors discovered that different definitions are provided by different standards within a common discipline and used differently across various disciplines. This paper raises the concern that a common understanding of terms and basic concepts has not yet been established to address the very specific technical issues facing SRA DI&C. Based on the lessons learned from the review of the definitions of interest and the analysis of dependency relationships existing between these definitions, this paper establishes a set of recommendations for the development of a consistent terminology for SRA DI&C. Highlights: ● We reviewed definitions of terms used in reliability analysis of digital systems. ● Different definitions are provided by different standards within a common discipline. ● Acyclic and cyclic structures of dependency in defining terms are compared. ● Three recommendations for the development of a consistent terminology provided.